2019
DOI: 10.1177/2516865719839011
|View full text |Cite
|
Sign up to set email alerts
|

Thymoquinone-Induced Reactivation of Tumor Suppressor Genes in Cancer Cells Involves Epigenetic Mechanisms

Abstract: The epigenetic silencing of tumor suppressor genes (TSGs) is a common finding in several solid and hematological tumors involving various epigenetic readers and writers leading to enhanced cell proliferation and defective apoptosis. Thymoquinone (TQ), the major biologically active compound of black seed oil, has demonstrated anticancer activities in various tumors by targeting several pathways. However, its effects on the epigenetic code of cancer cells are largely unknown. In the present study, we performed R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 74 publications
3
30
0
Order By: Relevance
“…This is consistent with previous investigations suggesting that thymoquinone could reverse DNA hypermethylation in cancer cells [44,45]. Another recent study demonstrated that thymoquinone can decrease the expression of some important epigenetic proteins like DNMT1,3A,3B and HDAC1 in Jurkat cells and breast cancer cells [46]. In fact, it has been recently speculated that because of its structure, thymoquinone could act as both a demethylating and methylating agent [45].…”
Section: Discussionsupporting
confidence: 91%
“…This is consistent with previous investigations suggesting that thymoquinone could reverse DNA hypermethylation in cancer cells [44,45]. Another recent study demonstrated that thymoquinone can decrease the expression of some important epigenetic proteins like DNMT1,3A,3B and HDAC1 in Jurkat cells and breast cancer cells [46]. In fact, it has been recently speculated that because of its structure, thymoquinone could act as both a demethylating and methylating agent [45].…”
Section: Discussionsupporting
confidence: 91%
“…TQ-mediated anticancer activity has also been shown to involve epigenetic suppression or activation of specific genes [57,146,147]. TQ-induced p73 has been shown to represses the expression of the anti-apoptotic epigenetic integrator known as ubiquitin-like-containing PHD and RING finger domains (UHRF1) and its partner DNA methyltransferase 1 (DNMT1) [57,69].…”
Section: Epigenetic Modulation Of Gene Expression By Tqmentioning
confidence: 99%
“…Many purified components extracted from medicinal plants have shown beneficial therapeutic potentials in the recent years and widely used as an alternative to chemical drugs. Thymoquinone (TQ), the major bioactive component of the essential oil of black seeds have shown promising inhibitory effects on a large number of solid and leukemia tumors through targeting several pathways such as those involved in cell cycle, apoptosis, ROS generation, metastasis and angiogenesis [21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%